Analisis Penerapan Safety Management System di Gembira Loka Zoo - Hermawan, Budi; Sabila, Nourma Fitria (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Safety visitors in the world of tourism is a top priority that travel service providers must consider to the visitor to minimize accidents. Moreover, a zoo with the main attraction of its animal collection can also be a risk to visitors. Implementing the safety management system is essential to be applied in tourism management to provide visitors safety protection, so they feel safe and comfortable when they are travelling and are willing to come back to visit the zoo. This study uses a qualitative descriptive method carried out at Gembira Loka Zoo. The results showed that Gembira Loka Zoo had implemented a safety management system in tourism management by covering POAC (planning, organizing, actuating and controlling) based on eight indicators. It consists of exhibit design, distance and exhibit enclosures, warning boards, monitoring, sanitation, health and medicine, boredom, saturation and fear.